Investigating language learners' emotion-regulation strategies with the help of the vignette methodology. (June 2020) - Bielak, Jakub; Mystkowska-Wiertelak, Anna
Abstract: The emotions experienced and the emotion-regulation strategies (ERS) used by English majors (freshmen and sophomores; L1 Polish; n  = 133) enrolled in a Polish university in relation to their learning of English or another foreign language were investigated. The primary data collection tool was a new scenario-based questionnaire ( Managing Your Emotions for Language Learning [ MYE ]) which uses the vignette methodology. Participants responded to nine scenarios typical of classroom language learning (LL) by specifying what emotions they would experience and what ERS they would use to increase positive and handle negative emotions. They also listed the ERS they had actually used and reported on their effectiveness. Semi-structured interviews were conducted with selected learner participants ( n  = 16) and their teachers ( n  = 9). It was found that the scenarios were realistic and that participants experienced a range of positive and negative emotions, sometimes simultaneously. A comprehensive list of ERS for LL was established informed by but more nuanced than previous taxonomies. The choice of ERS seemed to depend on specific situations, the learning context and participant characteristics. Both learner and teacher participants considered learners' ERS effective. The validity of MYE has been established and its potential pedagogic use was put forward.